Anti-Hong–Ou–Mandel interference by coherent perfect absorption of entangled photons. (1st December 2022) - Vetlugin, Anton N; Guo, Ruixiang; Soci, Cesare; Zheludev, Nikolay I
Abstract: Two-photon interference, known as the Hong–Ou–Mandel effect, has colossal implications for quantum technology. It was observed in 1987 with two photodetectors monitoring outputs of the beamsplitter illuminated by photon pairs: the coincidence rate of the detectors drops to zero when detected photons overlap in time. More broadly, bosons (e.g. photons) coalesce while fermions (e.g. electrons) anti-coalesce when interfering on a lossless beamsplitter. Quantum interference of bosons and fermions can be tested in a single—photonics platform, where bosonic and fermionic states are artificially created as pairs of entangled photons with symmetric and anti-symmetric spatial wavefunctions. We observed that interference on a lossy beamsplitter of a subwavelength thickness, or a coherent perfect absorber, reverses quantum interference in such a way that bosonic states anti-coalesce while fermionic states exhibit coalescent-like behavior. The ability to generate states of light with different statistics and manipulate their interference offers important opportunities for quantum information and metrology.